EFEKTIFITAS PENGUMPULAN ZAKAT PROFESI (STUDI PADA BAZNAS DI KABUPATEN MAROS) - Mujahidin, Mujahidin (Palita: Journal of Social Religion Research, 2018)
This research aimed to analyse National Zakat Agency (BAZNAS) of Maros Regency in exploring the potential of profession zakat in Maros Regency. The research design was field research and employed qualitative descriptive method. Instrument of this research were the interview guide, field note and recoding. The results of the research found that: 1) Maros Regency has a large potential of professional zakat. 2) Data shows that zakat collection is not optimal